Advanced water level meter for alerting about floods - Sandeep Naidu, Ram; Likitha Chowdary, Bodapati; Ravi Teja, Jujjuri; S.R. Prasad, M (International Journal of Engineering and Technology, 2018)
This smaller scale show is performed on the premise of a programmable electronic printed circuit AT MEGA Â 2560, an electronic circuit associated with electrical protections that are situated at a particular stature, inside a water holder: when the water level ascents and achieves the resistors, differs the impedance, the data from water level Â sensor is transmitted by means of Wi-Fi to a portable workstation, at that point this data is additionally observed in cell phones, where clients can see the water level in waterways. At last, the smaller scale demonstrates is tried by test tests under a controlled domain and attractive outcomes are acquired. The principle point of this task is to plan a framework which will screen and control the water level in the dams and furthermore suggest the concerned expert when the water level surpasses the farthest point.